2012
DOI: 10.4111/kju.2012.53.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Changing Trends in Medical Therapy on Surgery for Benign Prostatic Hyperplasia Over Two Decades

Abstract: PurposeFollowing the introduction of medical therapy for benign prostatic hyperplasia (BPH), we determined the effect of the change in trends in medical therapy on the indication and outcome of surgical intervention for BPH.Materials and MethodsWe compared the basic characteristics of, weight of resected tissue of, transfusions in, and postoperative complications of patients who underwent surgery between 1985 and 1989 (before the advent of medical therapy for BPH), between 1995 and 1999 (when medical therapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 23 publications
2
36
1
Order By: Relevance
“…They have increased operative risk of undergoing TURP/open surgery or refuse any surgical treatment 18. In this meta-analysis, for large volume (PV ≥80 mL) BPH, there were significant improvements in the IPSSs (−18.32 points), QoL scores (−2.50 points), PV (−47.58 mL), Q max (+6.00 mL/s) and PVR volume (−76.80 mL) after PAE during the 12-month follow-up, and there were no life-threatening complications.…”
Section: Discussionmentioning
confidence: 99%
“…They have increased operative risk of undergoing TURP/open surgery or refuse any surgical treatment 18. In this meta-analysis, for large volume (PV ≥80 mL) BPH, there were significant improvements in the IPSSs (−18.32 points), QoL scores (−2.50 points), PV (−47.58 mL), Q max (+6.00 mL/s) and PVR volume (−76.80 mL) after PAE during the 12-month follow-up, and there were no life-threatening complications.…”
Section: Discussionmentioning
confidence: 99%
“…Both groups had similar baseline characteristics, so that they were homogeneous for comparisons. Study subjects were men (average age: 65 years) with moderate BPH (IPSS values ≥ 7, but 19), and with several co-morbidities (hypertension diabetes, dyslipidemia and obesity) characteristic of this population [35,36]. Concomitant medications were consistent with the personal history of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, as the population ages, more and more people will require medical care. 11 Any delay in surgical therapy, when indicated, can cause progression of BPH and worsen its symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, significant comorbidities including increased body mass index, chronic medical diseases and operative history have increased in the last two decades for patients with symptomatic BPH. 10 In the current study, we compared 3 consecutive timebased groups of BPH patients surgically treated with different modalities of Holmium and GreenLight lasers, including ablation, incision and enucleation procedures. We found that preoperative prostate volume significantly correlated with age at surgery, total energy used at surgery, and the total operative time.…”
mentioning
confidence: 99%